Annual Energy Usage Reduction and Cost Savings of a School: End-Use Energy Analysis - Aiman Roslizar; M. A. Alghoul; B. Bakhtyar; Nilofar Asim; K. Sopian (The Scientific World Journal)
Buildings are among the largest consumers of energy. Part of the energy is wasted due to the habits of users and equipment conditions. A solution to this problem is efficient energy usage. To this end, an energy audit can be conducted to assess the energy efficiency. This study aims to analyze the energy usage of a primary school and identify the potential energy reductions and cost savings. A preliminary audit was conducted, and several energy conservation measures were proposed. The energy conservation measures, with reference to the MS1525:2007 standard, were modelled to identify the potential energy reduction and cost savings. It was found that the school’s usage of electricity exceeded its need, incurring an excess expenditure of RM 2947.42. From the lighting system alone, it was found that there is a potential energy reduction of 5489.06 kWh, which gives a cost saving of RM 2282.52 via the improvement of lighting system design and its operating hours. Overall, it was found that there is a potential energy reduction and cost saving of 20.7% when the energy conservation measures are earnestly implemented. The previous energy intensity of the school was found to be 50.6 kWh/m2/year, but can theoretically be reduced to 40.19 kWh/mm2/year.